Plausible subjective experience versus fallible corroborative evidence: The formulation of insanity in Nigerian criminal courts - Ogunwale, Adegboyega; Pienaar, Letitia; Oluwaranti, Oluwaseun (Frontiers in Psychiatry, 2023)
Insanity as a defence against criminal conduct has been known since antiquity. Going through significant reformulations across centuries, different jurisdictions across the globe, including Nigeria, have come to adopt various strains of the insanity defence, with the presence of mental disorder being the causative mechanism of the crime as their central theme. A critical ingredient in the Nigerian insanity plea is the presence of ‘mental disease’ or ‘natural mental infirmity’ as the basis for the lack of capacity in certain cognitive and behavioural domains resulting in the offence. . Mental disorders, which are the biomedical formulations of this critical legal constituent are primarily subjective experiences with variable objective features. Using illustrative cases based on psycho-legal formulation as well as reform-oriented and fundamental legal research, it is shown that Nigerian courts have held that claims of insanity based on the accused person’s evidence alone should be regarded as “suspect” and not to be “taken seriously”. Thus, Nigerian judicial opinions rely on non-expert accounts of defendants’ apparent behavioural abnormalities and reported familial vulnerability to mental illness, amongst other facts while conventionally discountenancing the defendants’ plausible phenomenological experiences validated by expert psychiatric opinion in reaching a conclusion of legal insanity. While legal positivism would be supportive of the prevailing judicial attitude in entrenching the validity of the disposition in its tenuous precedential utility, legal realism invites the proponents of justice and fairness to interrogate the merit of such preferential views which are not supported by scientific evidence or philosophical reasoning. This paper argues that disregarding the subjective experience of the defendant, particularly in the presence of sustainable expert opinion when it stands unrebutted is not in the interest of justice. This judicial posturing towards mentally abnormal offenders should be reformed on the basis of current multidisciplinary knowledge. Learning from the South African legislation, formalising the involvement of mental health professionals in insanity plea cases, ensures that courts are guided by professional opinion and offers a model for reform.